The dialogues between content and language: Cautions and challenges in the emergence of a bilingual education program - Carlos Eduardo Aguilar Cortés; Nelson Eduardo Alzate B. (Universidad de La Sabana, 2015)
This paper presents a set of ideas about the basics for developing interdisciplinary dialogues between content (science) and language (English) in bilingual educational processes, under the premise that a satisfactory relationship between those elements help guarantee successful content-based instruction (CBI) in its form known as sheltered instruction. Additionally, a practical example (based on a science curriculum) is presented to demonstrate some principles that inform approaches to teaching such content. Finally, based on the authors' interdisciplinary work and pedagogical experiences, some recommendations on teaching content and language in bilingual settings are presented in the form of cautions (a balance of actions) and challenges (prospects).